Real-time location based service for tracing mobile using Android Application (International Journal of Engineering and Computer Science, 2017)
The main theme of phone finder mobile application is to provide an android application to the users that act as antitheft as well as remote control too. This android application basic functionality is providing protection from the theft. The application has capacity to send the SMS along with location coordinates (longitude, latitude) to the registered mobile number. This application also has capable to execute the tasks by processing the SMS from the parent mobile (registered mobile).The user can control the mobile functionalities like WLAN, mobile modes (general, vibrate, silent).It has the capacity play an alert sound even through it was in silent mode. This helps the user to find the mobile if he misplaced somewhere in surroundings.